Midlands State University Law Review Vol.1 - Mubako, S. (ed); Madebwe, T.(ed); Tsabora, J.(ed) (2014)
The thematic focus of this Inaugural issue of the Midlands State University Law Review is “The Jurisprudential Promise of a New Constitutional Dispensation in Zimbabwe”. Motivating this theme was the fact that, on the 22nd May 2013, Zimbabwe adopted Constitution of Zimbabwe Amendment (No. 20) Act, 2013) which effectively ushered in Zimbabwe’s new national Constitution. The new Constitution replaced the old 1979 Lancaster House Constitution, which was published as a Schedule to the Zimbabwean Constitution Order 1979 (Statutory Instrument 1979/1600 of the United Kingdom) and had been amended a total of 19 times. Zimbabwean constitutional jurisprudence has long been based upon this old Constitutional framework and there is no doubt that such jurisprudence will not be entirely rendered archaic by the new constitutional framework. However, the new constitutional dispensation introduces the possibility of new trajectories in Zimbabwe’s constitutional jurisprudence. Indeed, it is hoped that this new Constitution will generate its own constitutional jurisprudence, in view of the different set of principles, values and norms that underpin it. Importantly, to law academics, legal practitioners and all stakeholders in Zimbabwe’s legal system, the dawn of this new constitutional system provides an interesting normative framework to analyse the new directions, ideas, values and principles embodied in various provisions of the new Constitution. As such, this issue of the Midlands State University Law Review is intended as a platform allowing law academics, legal practitioners and other stakeholders in Zimbabwe’s legal profession to progressively explore the meaning, possible impact and implications of the new Constitution on Zimbabwean law and society.